User Experience Analysis of E-Learning UIN Malang with User Experience Questionnaire (UEQ) Method: Case Study of Students of Library and Information Science Departmen - Listiyah, Alimatul (Proceedings of the International Conference on Green Technology, 2021)
Abstract -The rapid advancement of information technology has an impact on all aspects of human life. In the field of education, this can be seen through the number of universities that use E-Learning (Electronic Learning) as an alternative media of learning between lecturers and students, especially during this pandemic, where learning is done by online. One of the universities that utilizes E-Learning as media of learning is UIN Malang. Even though it is used as an alternative media of learning, there is still some troubles that experienced by students. According to a survey we conducted on students from the Department of Library and Information Science of UIN Malang, it was found that the use of E-Learning that owned by the campus was still low. The data shows that 53% of the 60 respondents do not use the application frequently. This study use a quantitative typeof research with asurvey approach. The population in this study is the students of Library and Information Science Department. The sample is part of the entire population that can represent the entire population. To determine the size of the sample to be taken, we used the Slovin formula with a confidence value of 90% and a tolerance value of 10%. In addition, based on a survey conducted using the User Experience Questionnaire (UEQ) method, it was found that in terms of attractiveness, perspicuity, efficiency, dependability, stimulation and novelty, are in a bad position. From the explanation above, it can be concluded that, E-Learning UIN Malang is still not optimally used and still needs a lot of development.